Біоінформатичний пошук елементів відгуку на гормони у промоторі гена О⁶ -метилгуанін-ДНК метилтрансферази (MGMT) - Нідоєва, З.М.; Самойленко, І.О.; Підпала, О.В.; Лукаш, Л.Л.; Яцишина, А.П. (Фактори експериментальної еволюції організмів, 2015)
Aims. The human DNA repair enzyme O⁶ -methylguanine-DNA methyltransferase (MGMT) protects cells against mutations and cell death. On the other hand, it causes the resistance of cancer cells to alkylating chemotherapy. Combination of the chemotherapy and the hormone therapy is widely-used for the treatment of many types of cancer. However, a little is known about effects of hormones on the MGMT transcription. Therefore, the aim of this study was to search the hormone response elements within human MGMT promoter. Methods. We performed in silico analysis of the human MGMT promoter (Х61657.1) to predict hormone response elements using different programs. Results. We predicted novel potential hormone response elements, including such for steroid hormones and thyroid hormone receptorlike factors. Conclusions. Question of a functional activity of the revealed potential elements and the regulation of the MGMT expression by hormones require further experimental studies.